Connectivity Defects and Collective Assemblies in Model Metallo‐Supramolecular Dual‐Network Hydrogels. Issue 1 (7th November 2019) - Ahmadi, Mostafa; Löser, Lucas; Fischer, Karl; Saalwächter, Kay; Seiffert, Sebastian
Abstract: Double network hydrogels are composed of chemical and physical bonds, whose influences on the macroscopic material properties are convoluted. To decouple these, a model dually crosslinked network with independently tunable permanent and reversible crosslinks is introduced. This is realized by interlinking linear and tetra‐arm poly(ethylenegycol) (PEG) precursors with complementary reactive terminal groups. The former also carries a terpyridine ligand at each end, which forms reversible metallo‐supramolecular bonds upon addition of metal ions. These dual networks display different types and amounts of network defects, as studied by light scattering and proton double‐quantum (DQ) NMR. Dynamic light scattering suggests that the network mesh size decreases upon introduction of metal ions, as supported by a decrease of the residual dipolar coupling constant in NMR. Static light scattering indicates larger static inhomogeneities in those networks composed of stronger ions. This is complemented by a fast solid‐like component in the DQ buildup in NMR, attributed to the formation of nanoscopic clusters of charged complexes. The DQ buildup curves also suggest that the presence of strong physical bonds increases the fraction of mobile segments, like loops and dangling ends. This combined study unveils the interplay of chemical and physical bonds toward the formation of a hierarchical structure. Abstract : Different types of structural inhomogeneities in a model dual‐network hydrogel with permanent and reversible crosslinks are studied on global and local scales by light scattering and proton double‐quantum NMR, respectively.